The impact of Compensation and Work Environment towards the Employee Performances Mediated by the Job Satisfaction - Mellasanti - Ayuwardani (Admisi dan Bisnis, 2021)
The purpose of this research is to measure the impact of compensation and work environment towards the employee performances mediated by the job satisfaction. This is an Explanatory Research. The population in this study were employees totaling of 106 people. The sample of this research is 83 people. Data collecting techniques used was questionnaire, and analyzed using SPSS. The results of this study indicate that job satisfaction mediates the effect of compensation on employee performance partially and job satisfaction mediates the effect of work environment on employee performance absolutely or perfectly